The McCollough Facial Rejuvenation System: Expanding the Scope of a Condition-Specific Algorithm - McCollough, E. Gaylon; Ha, Chi D. (Facial Plastic Surgery, 2012)
The ideal facial rejuvenation algorithm is comprised of an appropriate combination of procedures, thoughtfully chosen from an assortment of reliable alternatives, that when skillfully performed provide both short- and long-term enhancement to the undesirable conditions of aging that exists at the time of treatment. In 2010, the senior author published the first scientific article in which a condition-specific classification system and a treatment plan algorithm were applied to the discipline of facial rejuvenation. In the landmark article, the senior author reviewed his surgical experience of more than 5000 face-lifts and grouped patients into five major categories (or stages), based upon the extent of aging identified in various regions of the face and neck and the procedures performed to correct them. The criteria (that have now been suggested on a facial aging worksheet) were recorded in a data blank comprised of a first-generation worksheet. Once the data were collected—and using algorithmic charts for each region and/or facial feature—the most appropriate plan of action for a given patient was created. The sole objective in sharing the senior author's methodology was to launch a scholarly discussion among physicians and surgeons involved in the various disciplines that provide rejuvenation procedures on the face, head, and neck. From such a debate would, hopefully, emerge a definitive algorithmic system—one based squarely on the venerable ethics of medicine, coupled with the appropriate application of and skillful performance of the fundamental principles of surgery. A single, science-based system would restore order to a noble discipline, currently being challenged by narcissism, gimmickry, and commercialization. The implementation of a system rooted in universal truths would require its advocates to agree upon a common “language,” the implementation of which allows aesthetically focused surgeons to share both new ideas and time-tested experiences. More importantly, a condition-specific system matches each potential patient's problems—at every age—with the appropriate facial rejuvenation treatment plan, restoring the ideals of science and art to the profession. Initially provided in a consumer information book devised to assist patients with understanding the advantages of personalized treatment plans, the senior author later shared his practices and evolving system with colleagues attending conventions, seminars, and courses. Only after he was convinced that his system could be of benefit to physicians and surgeons from a variety of backgrounds was it offered to the peer-reviewed medical literature. Clearly, a plethora of techniques and materials are available for facial rejuvenation; however, only the ones deemed to be worthy of consideration were included. In practice—and in this presentation—the authors expanded the scope of the previously published article and offer a user-friendly, condition-specific worksheet and algorithmic tables designed to make it easier for surgeons to select the right combinations of procedures—at the right time in a patient's life. Although imitations potentiate an environment of disharmony, the authors remain committed to enabling the evolution of a single facial rejuvenation classification system, one that—with the input of like-minded scholars—could restore needed order to a branch of the medical profession that, in recent years, seems to have lost its focus.
Keywords: rejuvenation; classification; biological age; treatment algorithm